2005
DOI: 10.1016/j.febslet.2005.07.063
|View full text |Cite
|
Sign up to set email alerts
|

2.45 GHz radiofrequency fields alter gene expression in cultured human cells

Abstract: The biological effect of radiofrequency (RF) fields remains controversial. We address this issue by examining whether RF fields can cause changes in gene expression. We used the pulsed RF fields at a frequency of 2.45 GHz that is commonly used in telecommunication to expose cultured human HL-60 cells. We used the serial analysis of gene expression (SAGE) method to measure the RF effect on gene expression at the genome level. We observed that 221 genes altered their expression after a 2-h exposure. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 37 publications
4
49
0
Order By: Relevance
“…In MW therapy, conversive heat using 0.3-3.0 GHz of electromagnetic wave (2.45 GHz is typically used for clinical applications) is applied to a target area using a magnetron tube via an applicator, and is believed to be effective in increasing deep temperature. Although MW has nonthermal effects on cellular biological activity (e.g., apoptotic-related signaling and cell cycle), 17 it has been shown that MW was useful to deliver heat stimulation to deep tissues in the articular joint. 18 MW therapy is a well-recognized treatment modality for joint disease and is widely used in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…In MW therapy, conversive heat using 0.3-3.0 GHz of electromagnetic wave (2.45 GHz is typically used for clinical applications) is applied to a target area using a magnetron tube via an applicator, and is believed to be effective in increasing deep temperature. Although MW has nonthermal effects on cellular biological activity (e.g., apoptotic-related signaling and cell cycle), 17 it has been shown that MW was useful to deliver heat stimulation to deep tissues in the articular joint. 18 MW therapy is a well-recognized treatment modality for joint disease and is widely used in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the hazardous effects of EMFs on living systems are increasing (Berg, 1995;Goodman et al, 1995). It has been documented that EMFs affect the cell protein (Kwee et al, 2001), change the cell membrane characteristics (Goltsov, 1999), and alter the enzyme activity (Paulraj and Behari, 2002;Barteri et al, 2004) and gene expression (Lee et al, 2005) in animals. Additionally, radiofrequency EMFs induce lipid peroxidation and heat shock proteins, and elicit antioxidant response in human cells (Kwee et al, 2001;Moustafa et al, 2001;Leszczynski et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of 2.45 GHz high frequency electromagnetic field to glioma cells at SAR levels above 20 W/kg led to an increased level of HSP70, even when the effect of raised temperature is taken into account (Tian et al, 2002 radiation at 10 W/kg of SAR for 2∼6 h affected expression of 221 genes including apoptosis-related genes and the cell cycle genes in human HL60 cells without significant increase of HSP expression (Lee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%